Teensy 마이크로 컨트롤러 기반 산소 유량 제어기 개발 및 성능평가 - 유민상; 장연숙; 김무환; 조성보; Yu, Min Sang; Jang, Yeonsook; Kim, Muhwan; Cho, Sungbo (Journal of biomedical engineering research, 2021)
Flowmeter and oxygen sensors are listed in COVID-19 essential medical devices. This article reports a Teensy microcontroller-based Oxygen mass flow controller (MFC), core part of the oxygen respirator or extracorporeal membrane oxygenation (ECMO). The developed MFC consisting of the microcontroller, MEMS flow sensor, and solenoid valve was able to accurately control 0 to 100 sccm of oxygen flow rate. The pressure of vacuum chamber increased proportionally to the flow rate (0.998 of Pearson correlation coefficient). The experimental results proved that the developed MFC exhibits comparable performance to a commercial MFC in accuracy, settling time, linearity with pressure, and repeatability of oxygen mass flow control. It is expected that this simple and cheap MFC is utilized for oxygen therapy against the severe acute respiratory syndrome coronavirus 2.